(3CUhd JQcjH GdCOhjIs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdaGVdH eMeO Hf Ydi GdSeQbfOi Ef GdhGLH Ydi cd Pi dH Cf jJbQH Edi Gddg hjJhSd Edjg hCMSf GdhSGFd hCLhO GdPQGjY EeJKGd GdChGeQ hGdfhGgi eGjYhO Ydi faY GdfGS YGeg s
(3BNQgG (B:s
(3aUd ai CSHGH GdEMSGS hGdESJaQGZ ,SHH GdEMSGS VYa GdOGaYI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B40 - (3U(B86s
(3fSNI NGeSI fajSI ef GdbSe GdKGdK ef GdfLjHGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
(3agQS GdWH (B- (3U (B195 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B271 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs